Hydrogen-bonded porous frameworks constructed by rigid π-conjugated molecules with carboxy groups - Hisaki, Ichiro (Journal of inclusion phenomena and macrocyclic chemistry, 2020)
This review covers construction and properties of porous molecular crystals (PMCs) constructed through hydrogen-bonding of C 3 -symmetric, rigid, π-conjugated molecular building blocks possessing carboxyaryl groups, which was reported in the last 5 years by the author’s group. PMCs with well-defined, self-standing pores have been attracted attention due to various functionalities provided by selective and reversible inclusion of certain chemical species into the pores. However, it has been recognized for long time that construction of PMCs with permanent porosity is not easy due to weakness of noncovalent intermolecular interactions. Systematic construction of PMCs have been limited so far. To overcome this problem, the author has proposed a unique molecular design concept based on C 3 -symmetric π-conjugated molecules (C 3 PIs) possessing o -bis(4-carboxyphenyl)benzene moieties in their periphery and demonstrated that C 3 PIs systematically yielded hydrogen-bonded organic frameworks (HOFs) composed of H-bonded 2D hexagonal networks (H-HexNets) or interpenetrated 3D pcu -networks, which exhibit permanent porosity, significant thermal stability, polar solvent durability, robustness/flexibility, and/or multifunctionality.